Energy, exergy and exergoeconomic analyses of a combined supercritical CO2 recompression Brayton/absorption refrigeration cycle. (15th September 2017) - Wu, Chuang; Wang, Shun-sen; Feng, Xue-jia; Li, Jun
Highlights: An exergoeconomic analysis is performed for the SCRB/ARC cycle. Parametric analysis is performed to study the performance of the SCRB/ARC. Performances of the SCRB/ARC and SCRBC are presented and compared. The SCRB/ARC has better performances in comparison with the SCRBC. Abstract: Exergoeconomic analysis is performed for a novel combined SCRB/ARC (supercritical CO2 recompression Brayton/absorption refrigeration cycle) in which the waste heat from the SCRBC is recovered by an ARC for producing cooling. Parametric analysis is conducted to investigate the effects of the decision variables on the performance of the SCRB/ARC cycle. The performances of the SCRB/ARC and SCRBC cycles are optimized and compared from the viewpoints of first law, second law and exergoeconomics. It is concluded that combining the SCRBC with an ARC can not only enhance the first and second law efficiencies of the SCRBC, but also improve the exergoeconomic performance. The results show that the largest exergy destruction rate occurs in the reactor, while the components in the ARC have less exergy destruction. The reactor and turbine are the first and second important components from exergoeconomic aspects. When optimization is based on the exergoeconomics, the first and second law efficiencies and the total product unit cost of SCRB/ARC are 26.12% higher, 2.73% higher and 2.03% lower than those of the SCRBC. The optimization study also reveals that an increase in the reactor outlet temperature can enhance both thermodynamic and exergoeconomic performances of the SCRB/ARC. For the basic design case, the SCRB/ARC can produce 71.76 MW of the cooling capacity and 6.57 MW of the cooling exergy at the expense of only 0.36 MW of power in comparison with the SCRBC.